Teachers' Efforts to Improve Students' Ability to Read the Qur'an - Hasibuan, Saiful Anwar; Pasaribu, Muksana; Rosmaimunah, Rosmaimunah (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
This study aims to analyze the strategies teachers use to improve students' Qur'an reading skills, identify the obstacles faced during the learning process, and explain the outcomes of teachers' efforts in enhancing students' abilities. A descriptive qualitative approach was employed, with data collected through classroom observations, interviews with teachers, students, and the head of the madrasah, as well as documentation such as student learning outcome reports. The study was conducted at Madrasah Anshoriah Al-Islamiyah, Songkhla, Thailand. Findings reveal that teachers implemented practice-based learning methods, individual mentoring, and varied learning media to improve students' Qur'an reading skills. However, challenges such as differences in student abilities, limited instructional time, and a lack of motivation among some students were identified. To address these issues, teachers employed diverse teaching methods, provided individual support for struggling students, organized Tahfidz and Tilawah programs, and involved parents in the learning process. These efforts resulted in a gradual improvement in students' Qur'an reading abilities, demonstrating the effectiveness of the implemented strategies. Students who initially struggled with reading the Qur'an showed progress with proper guidance and methods. An individualized approach enhanced fluency and tajwid comprehension, while the use of technology made learning more engaging. Additionally, parental involvement at home played a crucial role in motivating students to practice consistently.